A theoretical study based on DFT calculations on the different influence of functional groups on the C–H activation process via Pd-catalysed β-X elimination. Issue 40 (15th September 2022) - Xiang, Xin; Zhao, Zeng-Xia; Zhang, Hong-Xing
Abstract : The energy decomposition analysis (EDA) results show the quantitative contribution of nucleophile groups in intramolecular interactions. Abstract : We have performed a series of theoretical calculations for palladium-catalyzed β-X elimination reactions. The DFT calculation combined with energy decomposition analysis shows the determining factors of reactivity. Such as, the elemental composition, the structure of different functional groups and the stronger steric repulsions contribution.